Urine metabolomics reveals biomarkers and the underlying pathogenesis of diabetic kidney disease: nephrology : original paper - Luo, Maolin; Zhang, Zeyu; Lu, Yongping; Feng, Weifeng; Wu, Hongwei; Fan, Lijing; Guan, Baozhang; Dai, Yong; Tang, Donge; Dong, Xiangnan; Yun, Chen; Hocher, Berthold; et al. (International urology and nephrology, 2023)
Diabetic kidney disease (DKD) is the most common complication of type 2 diabetes mellitus (T2DM), and its pathogenesis is not yet fully understood and lacks noninvasive and effective diagnostic biomarkers. In this study, we performed urine metabolomics to identify biomarkers for DKD and to clarify the potential mechanisms associated with disease progression.
Online veröffentlicht: 18. Oktober 2022
Gesehen am 08.07.2024